Hyperbranched polyester polyol modified with polylactic acid as a compatibilizer for plasticized tapioca starch/polylactic acid blends (2018)
A hyperbranched polyester polyol of the second generation (HBP2) was modified with polylactic acid (HBP2-g-PLA) and employed as a compatibilizer for plasticized tapioca starch (TPS)/polylactic acid (PLA) blends. The effect of the compatibilizer HBP2- g-PLA was evaluated in comparison to the control sample (TPS/PLA blend without HBP2-g-PLA). The torque value of the TPS/PLA blends with HBP2- g-PLA was lower than that of the control sample, while thermal stability and crystallinity followed opposite behavior. The glass transition temperature (Tg) and degree of crystallinity of the TPS/PLA blends with HBP2-g-PLA decreased with increasing mass fraction of HBP2-g-PLA. By scanning electron microscopy (SEM), it was observed that the morphology of the TPS/PLA blends with HBP2-g -PLA was more homogeneous than that of the control sample, confirming that HBP2- g-PLA acted as a compatibilizer and plasticizing agent to the TPS/PLA blends. Rheological analysis of the compatibilized TPS/PLA blends indicated the presence of microstructure.